INFLUENCING OF VITAMINOPROPHYLAСTIC COURSE BY PREPARATION «VITAM» ON INFORMATIVE AND NEYRO-VEGETATIVE COMPONENTS OF RELIABILITY OF HIGH-TENSE OPERATORS’ WORK - Apykhtin, K.A.; Shvets, A.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
For revealing of influence features of «Vitam» prophylactics course on information and neurovegetative components of operator’s highly reliability activity investigates 23 operators of the Call-centre in psycho-emotion simulated conditions model have been investigated. The psychophysiological functions of dynamic memorizing, moving object reactions, short-term memory and attention quality for a different level of complexity have been studied. There was performed research about influencing of vitamin-mineral complex «Vitam» on the vegetative neuro-humoral  adjusting of cardiac  rhythm and objective  indexes of mental capacity in the operators. It was found stress-protective effect (by reduction of amplitude of neuro-vegetative displays of stress reaction) and effect of mental work reliability improvement.